The Formative Assessment Analysis: A Case Study at Madrasah Aliyah Masyariqul Anwar Bandarlampung - Romadon Romadon; Achril Zalmansyah; Riswanti Rini (Journal of Educational Research, Evaluation and Supervision, 2024)
The research, titled "Analysis of Formative Assessment at Madrasah Aliyah (MA) Masyariqul Anwar, Bandarlampung" investigates the knowledge and application of formative assessment among teachers at MA Masyariqul Anwar in Durianpayung, Bandarlampung. Formative assessment is a critical component of modern teaching, aimed at enhancing student learning by identifying progress and providing targeted feedback. This study uses a qualitative descriptive method to explore the understanding, experiences, and perceptions of seven teachers through in-depth interviews, offering a detailed look into their classroom practices and challenges. The findings reveal varying levels of familiarity and proficiency among the teachers in implementing formative assessment. While some demonstrate a strong understanding and employ diverse strategies such as quizzes, group work, and peer reviews, others show limited knowledge and face challenges, including time management, resource availability, and inconsistent student engagement. Despite these hurdles, the research highlights a shared acknowledgment among teachers of the value of formative assessment in improving learning outcomes by fostering student-centered approaches and critical thinking. The novelty of this research lies in its specific focus on formative assessment practices within the context of Madrasah Aliyah, an Islamic secondary school. It provides fresh insights into how such assessments are perceived and implemented in a unique educational setting. The study concludes that effective formative assessment requires teachers to select suitable methods aligned with their classroom needs, supported by continuous professional development and institutional backing. These findings contribute to the broader discourse on formative assessment by emphasizing the need for context-specific strategies in diverse educational environments.